Exploring the Alignment Space – Lexical and Gestural Alignment with Real and Virtual Humans - Bergmann, Kirsten; Branigan, Holly P.; Kopp, Stefan (Frontiers in ICT, 2015)
Communication is characterized by speakers' dynamic adaptations and coordination of both linguistic and nonverbal behaviors. Understanding this phenomenon of alignment and its underlying mechanisms and processes in both human-human and human-computer interaction is of particular importance when building artificial interlocutors. In this paper we contribute to the exploration of the still fragmentary alignment space with two controlled experiments on lexical and gestural alignment. Our results show, on the one hand, that human interlocutors align their lexical choice and gesture handedness in similar ways when interacting with real versus virtual humans. On the other hand we found, however, also subtle differences. We discuss our findings in terms of a dynamic interplay of multiple components (automatic and strategic) and mechanisms (communicative and social) of alignment.